Sistem Informasi Rekrutmen Staff dan Internship Pada PT. Texmura Menggunakan Metode Prototype - Antonius, Antonius; Apriani, Rika; Baydhowi, Muhamad (INFORMATION MANAGEMENT FOR EDUCATORS AND PROFESSIONALS : Journal of Information Management; Vol 9 No 1 (2024): INFORMATION MANAGEMENT FOR EDUCATORS AND PROFESSIONALS (JUNI 2024), 2024)
Technological advancements have significantly impacted the productivity of companies in various fields, including the recruitment process. PT. Texmura, a construction company based in Jakarta, faces challenges in its recruitment process, which still relies on manual methods using platforms like Google Forms and email. This situation results in unstructured applicant data, requires time-consuming manual verification, and increases the risk of human error in data entry, which in turn can lead to inaccuracies. This study aims to design a web-based information system that can simplify and optimize the recruitment process for both staff and interns at PT. Texmura. The research method used is the prototype method, which has the advantage of producing an initial model that can be tested and evaluated by users, allowing for continuous improvements based on feedback until an optimal and tailored solution is achieved. This study results in a web-based recruitment information